2020
DOI: 10.1002/pi.5971
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the addition of ultrasound‐pulsed gelatin to chitosan on physicochemical and antioxidant properties of casting films

Abstract: This study investigated the performance of chitosan based films with added, high‐intensity ultrasound‐pulsed, gelatins (42, 52, 71 and 84 W cm−2). The mechanical, structural, chemical and antioxidant properties were investigated, to evaluate the potential of ultrasound as a technique to improve film properties. The tensile strength and elastic modulus of films containing ultrasound‐pulsed gelatins showed a significant increase, while the elongation parameter showed a significant decrease. Micrographs showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…This may be because more TP particles are protected by the three-dimensional network structure composed of CS and nSA after ultrasonic treatment [45] . Cuevas-acuna et al [46] also found that short time and high amplitude high-intensity ultrasonication treatment could improve the free radical scavenging ability of chitosan-gelatin film. Here, the high DPPH free radical scavenging activity was mainly based on the synergistic effect of TP and CS.…”
Section: Resultsmentioning
confidence: 97%
“…This may be because more TP particles are protected by the three-dimensional network structure composed of CS and nSA after ultrasonic treatment [45] . Cuevas-acuna et al [46] also found that short time and high amplitude high-intensity ultrasonication treatment could improve the free radical scavenging ability of chitosan-gelatin film. Here, the high DPPH free radical scavenging activity was mainly based on the synergistic effect of TP and CS.…”
Section: Resultsmentioning
confidence: 97%
“…When taking the F0/0 film as control, the films F5/0.5, F5/1, F5/2, F5/5 and F5/10 were statistically different ( p < 0.05 by Dunnett’s test). Cuevas-Acuña et al [ 63 ] studied the antioxidant properties of chitosan–gelatin composite films by FRAP and found values ranging from ~300 to 600 µmol TE mg −1 of film. In another study, conjugated chitosan grafted with stearic acid and gallic acid exhibited an antioxidant activity by FRAP assay, expressed as IC50, ranging from ~141 to 367 µg mL −1 [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The açaí oil had an antioxidant capacity against the ABTS radical around 120.21 ± 2.77 mg TE g −1 , as shown in Figure 10 . Cuevas-Acuña et al [ 63 ] studied the antioxidant properties of chitosan–gelatin composite films by ABTS radical scavenging assay and found values ranging from ~200 to 900 µmol TE mg −1 of film. In another work, CS films incorporated with mango leaf extract presented an antioxidant capacity by ABTS radical scavenging assay ranging from ~2 to 8 µg GAE g −1 film [ 65 ].…”
Section: Resultsmentioning
confidence: 99%